Optical Measurement Method for Blade Profiles Based on Blade Self-Features - Wang, Zongping; Yin, Ming; Ou, Dengying; Xie, Luofeng; Liu, Haohao; Yin, Guofu (IEEE transactions on industrial electronics (1982), 2022)
Developing accurate and efficient measurement systems for blade profiles has always been a vital issue in blade manufacturing. Nowadays, optical-based systems for measuring blade profiles have attracted significant interest due to their high efficiency and flexibility. However, as key steps in optical measurement of blades, system calibration and establishment of measurement datum are normally accomplished based on calibration objects, which may introduce uncertainty and affect the accuracy of the measurement. In this article, we propose a novel method for blade-profile measurement based on blade self-features. A measurement system based on a four-axis platform and laser scanning sensor (LSS) is developed. A calibration method based on the blade datum plane feature is introduced to eliminate the pose error of the system without using additional calibration objects. A feature-matching algorithm based on the covariance matrix of the blade local leading-edge feature is further proposed to establish the measurement datum. The proposed method requires smaller system-motion space and fewer LSS viewpoints, which would improve the efficiency and flexibility of the measurement system. Furthermore, less error accumulation can be achieved using our method, thus, resulting in higher measurement accuracy. The experimental results reveal the feasibility and good practical application prospect of this method.